Implikasi Zakat Terhadap Perekonomian - Bramasta Dafa; Ilham Taufik Hidayat; A.N. Rohim (Jurnal Ekonomi Syariah Pelita Bangsa, 2022)
This study aims to examine the implications of zakat on the economic sector. In this study, the author used a descriptive qualitative method, which is an effort to find out the events in the object of study, then carried out with a library study approach (library research). Library research is a type of research that uses secondary data obtained from research results, books, journals, articles related to the research topic. While analysing the data using content analysis technique, which is a method used to find out a conclusion from a text. The results of this study show that the potential development of zakat can be implied by good distribution management so that it can be used as a solution to overcome poverty.